Suitability Analysis of Settlement in Mountainous Region using MCDA Techniques: Case Study of Dhorpatan Municipality - Karki, Sagar; Pokharel, Ranjee Prasad (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.